Garlic and sapphires : the secret life of a critic in disguise - Reichl, Ruth (New York : Penguin Books, 2006)
The editor-in-chief of "Gourmet" recounts her visits to some of the world's most acclaimed restaurants, both as herself and as an anonymous diner in disguise, to offer insight into the differences in her dining experiences.
Include index.
Keywords: Reichl, Ruth; Food writers -- United States -- Biography